KAJIAN HUKUM TERHADAP DEBITUR DALAM PELUNASAN KREDIT MENGENAI HAK TANGGUNGAN: Legal Study on Debtors In Credit Repayment Regarding Mortgage Rights - Akbar, Citra (Fakultas Hukum, Universitas Trisakti, 2024)
Economic life is inseparable from daily life in running a business to create prosperity, and one way to do this is through borrowing capital. However, obtaining capital is not easy; it requires a process and collateral to secure the loan. One of the avenues to obtain capital is through bank loans. Banks, as financial institutions, provide capital to facilitate access to credit. In this process, banks often require collateral. In the execution of credit facilities, debtors who have repaid business loan credits with collateral such as land certificates and building certificates at a bank are entitled to receive back the collateral that was handed over to the bank. The bank, as the creditor, has the obligation to return the collateral to the debtor who has fulfilled their obligations. However, there are cases where creditors do not return the debtor's collateral documents. In such cases, the legal recourse for the debtor to regain the collateral from the creditor will depend on factors such as the cancellation of the mortgage rights and the effort to reclaim the collateral if the creditor does not return the collateral documents.